Hepatitis C virus reinfection in patients on haemodialysis after achieving sustained virologic response with antiviral treatment. Issue 4 (13th November 2021) - Liu, Chen‐Hua; Peng, Cheng‐Yuan; Kao, Wei‐Yu; Yang, Sheng‐Shun; Shih, Yu‐Lueng; Lin, Chin‐Lin; Tsai, Meng‐Kun; Lee, Chih‐Yuan; Chang, Chun‐Chao; Wu, Jo‐Hsuan; Liu, Chun‐Jen; Su, Tung‐Hung; et al.
Summary: Background: Data are limited regarding the risk of hepatitis C virus (HCV) reinfection after treatment‐induced sustained virologic response (SVR) in patients on haemodialysis. Aims: To assess the risk of HCV reinfection among patients on haemodialysis with treatment‐induced SVR. Methods: Patients on haemodialysis patients who achieved SVR12 with interferon (IFN) or direct‐acting antiviral (DAA)‐based treatment received follow‐up at SVR24 and then biannually with HCV RNA measurements. HCV reinfection was defined as the resurgence of viremia by different viral strains beyond SVR12 . The low‐risk general population who achieved SVR12 and who underwent the same post‐SVR12 surveillance served as the reference group. Crude reinfection rates per 100 person‐years (PYs) were calculated. Multivariate Cox regression analysis was performed to estimate the relative risk of HCV reinfection between the two groups. Results: We recruited 374 patients on haemodialysis and 1571 reference patients with a mean post‐SVR12 follow‐up of 4.7 and 6.1 years. All haemodialysis patients who achieved SVR12 also achieved SVR24 . The incidence rates of HCV reinfection were 0.23 per 100 PYs (95% confidence interval [CI]: 0.09‐0.59) in haemodialysis patients and 0.16 per 100 PYs (95% CI: 0.10‐0.26) in the reference group. The risk of HCV reinfection in patients on haemodialysis was comparable to that in the reference patients (hazard ratio [HR]: 1.39; 95% CI: 0.44‐4.38, P  = 0.57). Conclusions: The risk of HCV reinfection in patients on haemodialysis who achieve SVR12 is low and comparable to that in the low‐risk general population. HCV microelimination in this special population is feasible once universal screening and scaled‐up treatment are implemented. Abstract : 374 haemodialysis patients, 1571 low‐risk general population (reference) achieving SVR12 by DAAs or IFN.Incidence rate of HCV reinfection: Haemodialysis: 0.23 per 100 person‐years (PYs).Reference: 0.16 per 100 PYsHazard ratio (HR): 1.39 (95% CI: 0.44‐4.38, P  = 0.57).